A A Systematic Literature Review on the Use of Chat GPT in Higher Education: English - Latifah, Afina (Jurnal Inspirasi Pendidikan, 2024)
Technological developments are currently an important issue in education because they have given birth to Artificial Intelligence (AI), one of which is chat-gpt. Chat-gpt has had a significant impact on the world of education, especially in universities. This article aims to explore the use of chat-gpt in higher education, and then analyze the impacts and challenges of using chat-gpt. The research method used in this article is a Systematic Literature Review method (SLR). This study analyzes 18 relevant journal articles taken from various sources published in 2022-2023. This research highlights several uses of chat-gpt such as: in working on papers, articles, other scientific papers, and assignments given by lecturers. The research results show that the development of artificial intelligence technology has made chat-gpt often found among students. Almost all students use chat-gpt. because Chat-gpt provides many conveniences for students in terms of education. It can be concluded that the use of chat-gpt has an active role in helping students complete various kinds of tasks. And there are many challenges faced in using chat-gpt.